Observasi Sarana Terminal Brawijaya Banyuwangi Melalui Assessment Indikator Sanitasi Lingkungan Tahun 2019 - Dewi Firdanis; Nadiyah Rahmasari; Eqia Arum Azzahro; Nadya Reza Palupi; Pramudya Santoso Aji; Desi Natalia Marpaung; Ayik Mirayanti Mandagi (Poltekkes Kemenkes Yogyakarta, 2021)
Public places have the potential for disease transmission, environmental pollution, or other health problems, so sanitation is needed to create a clean environment in order to protect public health from the possibility of disease transmission and other health problems. Brawijaya Terminal is one of the public places crowded with the public to carry out transportation activities. The purpose of this research is to identify the general description of Brawijaya terminal sanitation in 2019. This research is a descriptive study with an observational approach that uses observation and interview methods to collect data. The instrument used in this study refers to the terminal sanitation inspection sheet instrument. The research instrument contains 5 variables, including the outside, the waiting room, sanitation facilities, occupational health and safety, and support. The results of the Brawijaya terminal sanitation research with 5 variables indicate that the Brawijaya terminal as a whole has met the terminal sanitation requirements with a total score of 1675 and is classified as good, namely 76.13%. For Brawijaya terminal sanitation to be maintained and to be even better, it is necessary to increase the sanitation variables which include latrines and urinals, hand washing facilities, and disposal of rainwater and dirty water.